Ekstraksi dan uji aktivitas antioksidan ekstrak etanol batang bintangur (calophyllum soulattri) - Fatimah, Siti; Widodo, Hernowo; Kustiyah, Elvi (Journal of Biopesticides and Agriculture Technology, 2024)
Background: Cigarette smoke, fried and grilled foods, excessive exposure to sunlight, motor vehicle fumes, certain drugs, toxins and air pollution are some sources of free radical compounds. As a result of homolytic breakdown, a molecule will break down into free radicals that have unpaired electrons. Electrons need a partner to balance their spin value, so that radical molecules become unstable and easily react with other molecules, forming new radicals. Findings: To prevent or reduce chronic diseases due to free radicals, antioxidants are needed. Antioxidants can slow down or inhibit the oxidation of substances that are easily oxidized even in low concentrations. Antioxidants can neutralize free radicals by donating one proton atom, making free radicals stable and non-reactive. Methods: Extraction is carried out by the maceration method, which is to soak the simplicia with ethanol solvent. This maceration process is carried out for 24 hours, then the solution containing the extract is filtered using filter paper. This maceration process is carried out three times. Conclusion: Ethanol extract of bintangur stem has quite high antioxidant activity, this can be proven by the IC50 value obtained of 3.05 ppm, this value is almost close to the IC50 value of vitamin C, which is 2.9 ppm, and by the appearance of spots in the Thin Layer Chromatography test.